Characteristics of Patchouli Plant (Pogostemon cablin Benth.) as An Antimicrobial in The Development of Dental Materials - Deviyanti Pratiwi; Decky Joesiana Indrani; Sunarso Sunarso; Ria Puspitawati (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Various natural ingredients have been developed in health science to avoid side effects that arise due to the use of chemicals. Pogostemon cablin Benth, or the patchouli plant, is a natural ingredient that has been researched and has potential as an antimicrobial and antioxidant in health problems. The development of natural materials in dentistry is influenced by their physical, chemical, and biological properties. This review aims to determine the various characteristic tests that need to be carried out to support the potential development of Pogostemon cablin Benth as an antimicrobial material in dentistry. Review: All parts of the patchouli plant can be used in the form of extracts and essential oils that contain secondary metabolites and other active ingredients, Patchouli Alcohol and its derivatives, which have an effect on antimicrobial activity. Another form of utilization of Pogostemon cablin Benth., such as emulsions, nanohydrogels, and encapsulations, aimed at increasing their activity. Various tests related to physical, chemical, and biological characteristics can be carried out to optimize the content of Pogostemon cablin Benth. so that it can be used appropriately, especially regarding health problems. Conclusion: The results of this search have provided an overview of Pogostemon cablin Benth, which has physical, chemical, and biological properties that have the potential to become antimicrobial materials for dentistry.